Stop Reaganism March and Rally Courthouse Park - Watkins, Howard::::::::: (1982)
Marchers turning into Courthouse Park; Michael Loring holding Sign to camera; June Loring in red/white dress with guide dog Cantor Michael Loring holding sign: "Don't Take Away Our Rights"